ANALISIS PROFIL KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI OPERASI BILANGAN BULAT KELAS VII - Buyung Buyung (MES: Journal of Mathematics Education and Science, 2021)
The purpose of this study was to analyze the profile of students' mathematical concept understanding abilities. This research is descriptive research. The strategy used is descriptive qualitative. This research was conducted at SMP Negeri 17 Sinkawang for the 2020/2021 academic year in class VII. The source of this research data is in the form of test results. The results of this study indicate that students' understanding of mathematical concepts with indicators restating a concept, the percentage obtained is 40% and falls into the low category. In the indicator of classifying objects according to the properties according to the concept, the percentage obtained is 33% and falls into the low category. The indicator presents the concept in various forms of mathematical representation, the percentage obtained is 57% and falls into the medium category. The results of this study indicate that the ability to understand the concept of Shiva is still low, it can be seen from the indicators used 2 of them are in the low category.